2011
DOI: 10.1007/s00795-010-0503-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitecture of the lamina muscularis mucosae and distribution of the lymphatic vessels in the human stomach

Abstract: The aim of the present study was to clarify the anatomical structure of the lamina muscularis mucosae (LMM) in the human stomach and to correlate it with the lymphatic spread of gastric cancer cells. Human stomachs taken at operation or autopsy were used. The specimens derived from these stomachs were examined by light microscopy immunohistochemistry and scanning electron microscopy (SEM). In the cardia and pyloric wall, bundles of smooth muscle cells of the LMM were relatively loose and thin and formed a reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Therefore, EGCs located at the upper/mid third of stomach might be more easily missed or diagnosed later than those in the lower third of stomach. The thickness of the submucosa has been reported to be thinner in the body than at the antrum [17], and the lymphatic capillaries are present just above the muscularis mucosa [18]. These anatomical factors may be associated with the submucosal invasive EGC located at the upper/mid third of the stomach as an increased risk for non-curative endoscopic resection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, EGCs located at the upper/mid third of stomach might be more easily missed or diagnosed later than those in the lower third of stomach. The thickness of the submucosa has been reported to be thinner in the body than at the antrum [17], and the lymphatic capillaries are present just above the muscularis mucosa [18]. These anatomical factors may be associated with the submucosal invasive EGC located at the upper/mid third of the stomach as an increased risk for non-curative endoscopic resection.…”
Section: Discussionmentioning
confidence: 99%
“…In the stomach, lymphatic vessels originate in the deep LP adjacent to the MM [7,8]. The diameter of lymphatic vessels tends to be larger as they enter the deep LP to the submucosal layer [18]. Thus, lymph node metastasis risk in gastric cancer might be different for cancers invading the LP or the MM because lymphovascular invasion is the most important risk factor in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the presence of large arteries and lymphatics in the submucosal layer [16]. Our patient had a medical history of endoscopic hemostasis for massive hematemesis, indicating carcinoma invasion below the muscularis mucosae at that time.…”
Section: Discussionmentioning
confidence: 71%